2019
DOI: 10.18632/oncotarget.27077
|View full text |Cite
|
Sign up to set email alerts
|

Real-world evidence to guide healthcare policies in oncology

Abstract: Randomized controlled clinical trials (RCTs) in oncology enroll patients who meet strict protocol-specified criteria. Many of these criteria overlap across multiple RCTs. A vast proportion of patients with metastatic cancer do not meet such criteria. Hence, patient populations encountered in clinical practice are essentially different from RCT-populations, questioning the representativeness of these trials. A real-world evidence approach, using data from clinical practice, is increasingly employed to complemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…This prospective real-world study presents long-term outcomes (≥ 3 years of follow-up) of patients with advanced melanoma treated with ipilimumab and other therapies. Safety outcomes and OS in patients treated with ipilimumab 3 mg/kg were similar to those previously reported in ipilimumab randomised clinical trials, despite the inclusion of patients who are typically excluded from randomised controlled trials (e.g., those with ECOG PS ≥ 2 or active/untreated brain metastases) [ 12 , 13 ]. This study also showed that patients who switched therapy (from ipilimumab or non-ipilimumab therapies) had longer OS than those who did not switch therapy.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…This prospective real-world study presents long-term outcomes (≥ 3 years of follow-up) of patients with advanced melanoma treated with ipilimumab and other therapies. Safety outcomes and OS in patients treated with ipilimumab 3 mg/kg were similar to those previously reported in ipilimumab randomised clinical trials, despite the inclusion of patients who are typically excluded from randomised controlled trials (e.g., those with ECOG PS ≥ 2 or active/untreated brain metastases) [ 12 , 13 ]. This study also showed that patients who switched therapy (from ipilimumab or non-ipilimumab therapies) had longer OS than those who did not switch therapy.…”
Section: Discussionsupporting
confidence: 70%
“…Although efficacy and safety results from randomised controlled trials of ipilimumab are available, data from long-term real-world studies are lacking. Real-world studies are being increasingly used to complement results from clinical trials as they represent patients who are diagnosed and treated routinely, including those who did not meet the selection criteria for registration into randomised controlled trials (e.g., patients with Eastern Cooperative Oncology Group performance status [ECOG PS] ≥ 2 or active/untreated brain metastases) [ 12 , 13 ]. Since the introduction of anti–PD-1 antibodies, which have shown superior first-line efficacy compared with ipilimumab [ 14 , 15 ], ipilimumab has been less commonly used as first-line monotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…A major strength of our population-based registry over the meta-analyses discussed in the introduction is that we also report data from patients with more advanced melanoma and a worse clinical performance score that do not meet the in- and exclusion criteria [ 25 , 26 ]. Another advantage of our registry is that we were able to adjust survival for patient baseline (tumor) characteristics and known risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…The previously mentioned meta-analyses included large randomized controlled trials, however, a vast proportion of patients with advanced melanoma treated in daily practice do not meet the in- and exclusion criteria of these trials [ 25 , 26 ]. Another limitation of these analyses was that the authors lacked additional information on patient-specific data, including the distribution of known risk factors among men and women [ 27 ]; this is important as the comparison between men and women in the setting of a randomized controlled trial can still be confounded, as it is not sex that is randomized.…”
Section: Introductionmentioning
confidence: 99%
“…13 This national cohort includes more than 13,000 men undergoing C-RT or H-RT in England, collected at least 18 months after diagnosis, providing contemporary evidence on functional outcomes from large-scale 'real-world' clinical practice. 14…”
Section: Introductionmentioning
confidence: 99%